2017
DOI: 10.1016/j.jhazmat.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Treatment technologies used for the removal of As, Cr, Cu, PCP and/or PCDD/F from contaminated soil: A review

Abstract: The contamination of soils by metals such as arsenic, chromium, copper and organic compounds such as pentachlorophenol (PCP) and dioxins and furans (PCDD/F) is a major problem in industrialized countries. Excavation followed by disposal in an appropriate landfilling is usually used site to manage these contaminated soils. Many researches have been conducted to develop physical, biological, thermal and chemical methods to allow the rehabilitation of contaminated sites. Thermal treatments including thermal desor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 154 publications
(215 reference statements)
0
28
0
Order By: Relevance
“…These results also showed that the contamination tends to decrease with depth (volume of contaminated soils less important in P2 compared with P1). These results can be explained by the fate and transport of metals, PCP and PCDD/F when they are released to the environment, due to the different physical and chemical properties of these contaminants and their different degree of affinity for the intrinsic components of soils (Guemiza et al, 2017). Besides, the results showed similarities in the estimations of the amounts of contaminated soils obtained by OK and SGS for PCP and PCDD/F unlike the other interpolation methods.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
See 1 more Smart Citation
“…These results also showed that the contamination tends to decrease with depth (volume of contaminated soils less important in P2 compared with P1). These results can be explained by the fate and transport of metals, PCP and PCDD/F when they are released to the environment, due to the different physical and chemical properties of these contaminants and their different degree of affinity for the intrinsic components of soils (Guemiza et al, 2017). Besides, the results showed similarities in the estimations of the amounts of contaminated soils obtained by OK and SGS for PCP and PCDD/F unlike the other interpolation methods.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…During the last decades, the amount of sites contaminated with inorganic and/or organic compounds dramatically increased. Therefore, challenges related to the rehabilitation of contaminated sites are becoming ubiquitous around the globe because of the serious health risks they represent as well as the significant costs involved (Guemiza et al, 2017). Treated wood storage sites are an example of areas of mixed contamination and are the subject of several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the monitoring and remediation of As and heavy metal contamination in Vietnam are of great interest to many concerned agencies and organizations, but the efficiency of these processes is very limited. Various physical and chemical methods have been developed worldwide for environmental pollution monitoring and remediation with positive results [18][19][20]. However, the disadvantages of these methods are their high cost and the potential for secondary pollution.…”
Section: Introductionmentioning
confidence: 99%
“…But as it was soon discovered, these procedures were in fact a source for a de novo polychlorinated compound synthesis, the process by which dioxins are re-formed being investigated in the recent years [17][18][19]. Therefore, greater attention was focused on more chemical-based processes [6,10,[20][21][22][23], along with microbial ones [24].…”
Section: Introductionmentioning
confidence: 99%